Working relationship between medical and sport science departments in football - An explorative study into English and German elite youth academies - Arenas, L.; Blessing, A. (Sport Performance & Science Reports, 2021)
The predominant aim of elite youth football academies is to develop players for the first team or at least generate income through the sale of marketable assets (1). The UEFA introduced guidelines for European football clubs, which impose minimum requirements for a club´s infrastructure, which lead to similar organizational structures across Europe (2). Thereby the three leading sectors of coaching, medical surveillance and sport science play a predominant role. In this context sports medicine evolved to a scientific discipline, which promotes an interdisciplinary commitment to the athlete (3). Nancarrow et al. (2013) provide a framework for quantifying interdisciplinary work by identifying ten characteristics and themes. Practical Applications • Need for more interdisciplinary work has already been demonstrated by several research groups • Research findings of the insufficiently detectable characteristics pointed out deficits at the strategic management process • Formulation of a mission statement can be viewed as entry point towards the multifaceted phenomenon of strategic management • A mission statement is a comprehensive concise statement defining what the organization does for whom, how and why